Fournier’s Gangrene 5-Year Experience and Validity of Fournier Gangrene Severity Index - Muhammad Jafar, Makil Shah, Javed Iqbal, Zia Ul Islam, Mansour Ullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To evaluate the validity of Fournier gangrene severity index in the assessment of disease severity. Materials and Methods: This Retrospective study was conducted in Pakistan Institute of Medical Sciences Islamabad. In this study we enrolled 35 patients with FG. The primary outcome in our study was mortality rate. Fournier’s Gangrene Severity Index was used to evaluate the severity of disease. The patients were divided into two group survival group and deceased group. Results: Total 36 patients with FG were enrolled, 80.6% were male and 29.4% were female with mean age of 43.30 ±10.5 years. The mortality rate was 19.4%. 41.7% patients had DM, 22.2% patients were smoker and 13.9% patients had high blood pressure. 61.1% cases had anal pain while 33.3% had scrotal pain. The patients were also distinguishing on the basis of origin and it was found that Proctological (72.2%), Urological (19.4%) and Gynecological (8.3%). Using an FGSI cut-off value > 9.5, we find out that the mortality rate was significantly higher in the group with a FGSI score >10 (100%). Practical implication: In this study we find out that FGSI is a reliable and excellent tool for the initial diagnosis of disease. So this study will help the clinical practioner to easily and at initial stages diagnose the disease. Conclusion: It is concluded that FGSI is a reliable and excellent tool for the initial diagnosis of disease. Keywords: Fournier's gangrene, Fournier's gangrene severity index, mortality